Assessing the implementation of healthy eating and physical activity policies and practices in the family day care setting: A cross‐sectional study. (7th October 2020) - Lum, Melanie; Grady, Alice; Falkiner, Maryann; Jones, Jannah; Finch, Meghan; Green, Sue; Herrmann, Vanessa; Hall, Alix; Yoong, Serene
Abstract: Issue addressed: While the family day care setting provides a unique opportunity to improve child health, few studies have assessed obesity prevention practices of this setting. This study aimed to examine the (a) prevalence of implementation of evidence‐based healthy eating and physical activity policies and practices among schemes (ie overarching governing agency) and educators in the family day care setting in Australia; and (b) associations between educator socio‐demographic characteristics and implementation of healthy eating and physical activity practices. Methods: Family day care schemes (n = 16) responsible for educators (n = 174) located in the Hunter New England region of NSW participated in a telephone survey in 2018, reporting their implementation of evidence‐based healthy eating and physical activity policies and practices. Linear mixed regression analyses were used to determine whether educator characteristics were associated with higher percentages of implementation. Results: Few schemes had comprehensive breastfeeding (0%) and screen time (19%) policies. However, the majority of educators (81%) communicated with families when lunchboxes were not consistent with guidelines. Educators implemented an average of 64.3% of practices assessed. Educators located in higher socioeconomic areas implemented a significantly higher percentage of practices than those in lower socioeconomic areas ( P  < .000). Educator years of experience was positively associated with percentage of implementation ( P  = .009). Conclusions: The implementation of obesity prevention policies and practices in the family day care setting is variable and associated with educator socio‐demographic characteristics. So what?: There is a need to support family day care schemes to improve their obesity prevention environments, particularly those related to policies.